2015
DOI: 10.3233/jpd-140424
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) or Paraquat on Core Temperature in C57BL/6J Mice

Abstract: Background: MPTP and paraquat are two compounds that have been used to model Parkinson’s disease in mice. Previous studies in two non-traditional strains of mice have shown that a single dose of MPTP can induce changes in body temperature, while the effects of paraquat have not been examined. Examination of body temperature is important since small fluctuations in an animal’s core temperature can significantly affect drug metabolism, and if significant enough can even culminate in an animal’s death.Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Administering acute MPTP regimens suitable for inducing stable and reproducible lesions of parkinsonism or parkinsonian syndrome showed that MPTP caused a rapid reduction in BW and a hypothermic effect in a dose-dependent manner, and unexpectedly high mortality rates in mice (at MPTP 20 mg/kg or higher) due to profound hypothermia in the absence of external heat support in a preliminary study (data not shown). These results are consistent with previous studies that reported hypothermic responses and sensitivity induced by unknown malfunctional cellular mechanisms, suggesting the need for external heat support in MPTP-induced PD mouse modeling [6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Administering acute MPTP regimens suitable for inducing stable and reproducible lesions of parkinsonism or parkinsonian syndrome showed that MPTP caused a rapid reduction in BW and a hypothermic effect in a dose-dependent manner, and unexpectedly high mortality rates in mice (at MPTP 20 mg/kg or higher) due to profound hypothermia in the absence of external heat support in a preliminary study (data not shown). These results are consistent with previous studies that reported hypothermic responses and sensitivity induced by unknown malfunctional cellular mechanisms, suggesting the need for external heat support in MPTP-induced PD mouse modeling [6].…”
Section: Discussionsupporting
confidence: 93%
“…To this end, rodent models for PD, particularly C57BL/6 mice, have been widely used to unravel various pathological events and explore therapeutic mechanisms, although humans and primates are the gold standard of PD research [3,4]. Over the years, with numerous efforts to develop a PD model in mice, the exogenous administration of a variety of neurotoxic materials such as 6-hydroxydopamine, paraquat, rotenone, and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) have been used to induce DA loss to replicate PD symptoms, collectively called parkinsonism and/or parkinsonian syndrome [5][6][7]. Among the various pharmacological PD models, the MPTP-induced PD model has been most commonly used for several reasons: similar clinical symptoms to those in patients with PD, no requirements for experimental technology, and reliable and reproducible lesions in the nigrostriatal dopaminergic pathway [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…MPTP dose volumes were 2.5 mL/kg/dose at WIL and 4 mL/kg/dose at SJCRH. Shoebox bin cages housing MPTP-treated animals housed at both SJCRH and WIL were placed on heating pads for 24 hours after dosing in order to maintain animal viability [25]. …”
Section: Methodsmentioning
confidence: 99%
“…High cell viability was found to be maintained up to 21 days in the spheroid model containing six cell types, which is useful in evaluating long term effects of drug toxicity [104]. Expression of P-gp and GLUT-1 proteins were also identified as these proteins have a pivotal role in expelling unwanted chemical from the brain tissue and transport glucose into the brain tissue respectively and abnormalities in these proteins lead to different diseases [104][105][106][107]. Expression of tight junctions, adherens junctions, and proteins associated with adherens junction was also identified to avert the free paracellular diffusion of substances into the brain parenchyma.…”
Section: Human Cortex Spheroid In Vitro Bbb Modelsmentioning
confidence: 99%